Evaluasi dalam Manajemen Diklat di Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Tengah - M Rizki Septianto; Abdul Gofur (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Evaluation plays an important role in education and training programs. Without evaluation, we cannot know the level of success of training participants and there will also be no opportunity for improvement. Education and training evaluation is a process to obtain information and data related to the learning outcomes experienced by training participants. The evaluation program in training includes principles, models, implementation, and follow-up. This evaluation has four levels and stages, namely: the evaluation planning stage, data collection, analysis, and reporting of evaluation results. Ultimately, training evaluation is used to make decisions about the benefits of the training program, whether the program will be continued or stopped, and what needs to be improved if the program is to be continued.